Optimizing Tableau for data visualization management by data analiyst at Kapanlagi Youniverse - Bifakhlina, Febriyanti; Perdana, Fitri; Prasetyadi, Abdurrakhman (Jurnal Informatio, 2025)
Backgroud: KapanLagi Youniverse (KLY) is an information institution and online media company that manages ten types of media with diverse segmentation. In this context, information management becomes crucial, especially considering that KLY has millions of users every day. One of the primary data sources is information about pageviews obtained through Google Analytics from all the websites managed. With pageviews reaching trillions, the management and distribution of data to stakeholders is essential. Purpose: This article aims to ensure that the data team managers at KLY can make informed decisions and provide valuable insights based on the available and accurate data for their users. To facilitate the management of large and complex data, the implementation of business intelligence is critical, with Tableau Server being used as a visualization tool for pageview data. This article discusses how optimizing the use of Tableau Server can enhance the effectiveness of data management and visualization at KapanLagi Youniverse, as well as its impact on better decision-making. Methods: This research employs a mixed approach that combines qualitative and quantitative methods to evaluate the use of Tableau Server in managing the visualization of pageview data. Results: The findings indicate that Tableau has proven effective in conducting in-depth data analysis, allowing for interactive exploration and the identification of patterns that are difficult to uncover through traditional methods, thereby supporting more informed and timely decision-making strategies.